EFEKTIVITAS MODEL PROBLEM-BASED LEARNING BERBASIS POLYA TERHADAP PENINGKATAN KEMAMPUAN PEMECAHAN SOAL CERITA MATEMATIKA SISWA SEKOLAH DASAR - Angrah Himni Diningrat, Alifvita Loista; Rizkasari, Elinda; Restuningsih, Ani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low capability of primary students in solving mathematical story problems stems from conventional instruction that fails to foster systematic reasoning. This quantitative study aimed to evaluate the effectiveness of the Problem-Based Learning (PBL) model in enhancing story problem-solving skills concerning data presentation materials structured around Polya’s framework. Employing a pre-experimental design (one group pretest-posttest design), the study involved a sample of 25 third-grade students at SDIT Bina Madina during the 2025/2026 academic year, selected via purposive sampling. Data were collected using a 5-item essay test validated empirically and demonstrating high internal consistency reliability (). The Shapiro-Wilk test satisfied the assumption of normality for both pretest () and posttest () scores. Inferential analysis using a paired-sample t-test revealed a statistically significant increase in mean scores from 50.08 () to 84.16 (), yielding (). The effect size calculation indicated a Cohen’s d of 2.806 (classified as a very large effect), supported by a mean Normalized Gain (N-Gain) score of 0.682 or 68.20% (moderately effective category). These findings provide empirical proof that PBL intervention effectively escalates elementary students' competencies in understanding, planning, executing, and evaluating mathematical story problem solutions.